Exploring the prospects of thermoelectric power generation in conjunction with a water heating system. (October 2015) - Faraji, Amir Y.; Goldsmid, H.J.; Dixon, C.; Akbarzadeh, A.
Abstract: Thermoelectric generators have long been recognized as a unique energy conversion device due to their capability to convert heat directly into electricity with no moving parts. Nevertheless, engineering applications of these solid-state devices, apart from specialised situations, have been limited by the relatively low intrinsic conversion efficiency of the thermoelectric materials. Many efforts have been made over recent years to improve the conversion efficiency of thermoelectric materials by increasing their figure-of-merit, with only marginal success. The authors recently introduced a novel combination of thermoelectric generators and liquid heaters to carry our two tasks in a manner that compensates for the low efficiency drawback of thermoelectric generators. The idea is to operate the thermoelectric generator in a symbiotic arrangement (a certain configuration of a combined heat and power generation mode – cogeneration) which consists of a stacked assembly of several thermoelectric modules sandwiched between cold and hot liquid passages appropriately connected to an ordinary liquid (e.g. water) heater. It was shown that the system can produce heat and electricity with nearly zero heat dissipation to the surroundings by re-using rejected heat from thermoelectric modules for inlet liquid preheating. In the present research, we aimed to extend our previous study and analyse the large-scale application of this kind of cogeneration system, including considerations of usefulness of this system in such large-scale applications and limitations of this cogeneration system. A theoretical estimation of the maximum achievable electrical power using this symbiotic system has been also presented. Highlights: A symbiotic thermoelectric/hot water system can produce electricity with no heat rejection. Large-scale TE power generation could be feasible through a symbiotic application. A water heater could supply enough heat for a TE generator apparatus to generate useful power. Implementation of the symbiotic system with a low flow rate of hot water may not be feasible.